Growth behavior and soil plant water relations as influenced by irrigation levels in barley genotypes - Verma, R. K.; Kumar, A.; Ghasal, P.C.; Thakaral, S.K. (Annals of Agricultural Research, 2018)
A field experiment was conducted during winter (rabi) season of 2011-2012 to study the effect of irrigation on growth and soil plant water relation of barley. The results revealed that irrigation and genotypes significantly influenced the phenology, growth of barley and soil plant water relations viz., leaf water potential, relative water content and soil moisture content. The growth parameters such as plant height, number of tillers and dry matter accumulation increased with the increase in irrigation frequency. In plant water relations, leaf water potential and relative water content was higher under two irrigations compared to one irrigation. Among the tested genotypes, plant height was highest in genotype BH 09-21(84 cm). Number of tillers were recorded highest in genotypes BH 08-36 (113) followed by BH 08-16 (107). Similarly, maximum leaf area index was recorded in BH 902 (5.21) as compared to other remaining genotypes. Interaction effect was also observed between irrigation and genotypes with respect to leaf water potential. At one irrigation, genotype BH 09-44 (-1.74 MPa) and BH 08-36 (-2.06 MPa) showed highest and lowest leaf water potential, respectively. Whereas genotype BH 09-05 (-1.60 MPa) showed the highest leaf water potential at two irrigation levels. Genotype BH 05-20 (82.96%) and BH 08-16 (87.03%) registered maximum relative water content at one and tow irrigations, respectively. The interaction between irrigation and barley genotypes was also significant for most of the characters indicating differential behavior of barley genotypes to two irrigation levels.